An approximate method for estimating rocket trajectory elements - Thiruvenkatachar, V. R. (Defence Science Journal, 2014)
In this paper the problem of using composite heptatubular charges in conventional guns for a linear law of burning has been discussed. A solution of the basic equations of Internal Ballistics has been derived under certain conditions, viz., the value of the radio of specific heats, has been assumed to be the same for both the charges and the covolume correction have not been neglected.